EPHEMERAL SPACES AS A PLACE OF CULTURAL EXPERIENTIAL SUPPORT.: CASE STUDIES: ESCENOGRAFÍA NOEL Y ÁRBOL NAVIDEÑO. (REVISTA NODO, 2023)
This project seeks to recognize the impressions that two ephemeral spaces left on its visitors as an extension of the inhabited space; contextualized in the celebration of Christmas on a citizen scale: the Christmas Show Noel and the Christmas Lighting of Envigado. Identifying the emotions that users experienced in their different pavilions, the description of the spatial factors that caused an impact on visitors to these ephemeral Christmas projects, in addition to the relationship of the different sensations generated by the spatial experience, as well as their effects on the remembrance of events.The present research was carried out based on the interpretive phenomenological methodology to achieve a qualitative analysis through a bibliographic and documentary review, also structured and semi-structured interviews. As well as the design of tests in the neuromarketing laboratory and a / b testing. This was done to find the synchrony between volunteers who are seeking these types of venues, as well as the opinion of experts against the recognition of the impressions that ephemeral cultural spaces achieve on visitors and designers.In conclusion, ephemeral cultural spaces, despite their short existence, can mediate between aspired permanence and are qualified by experience. This type of space can represent the cultural moment of their immediate society. The design of the experience should make an impression, or not, in the memory of the visitors, through astonishment, the nostalgia of the ephemerality of the event, to achieve an extension in time of the space that is no longer there.
Keywords: ephemeral architecture; culture; experience; phenomenological perception; time